Enhancing Students’ Social Intelligence through Tudang Sipulung Learning Model - Zahrawati B, Fawziah; Jumaisa; Arent, Ease; Aras, Andi (IAIN Madura, 2025)
Social intelligence is essential for students to engage effectively in collaborative and culturally responsive learning. This study aims to examine the effectiveness of the Tudang Sipulung learning model enhancing the social intelligence of students in the Social Studies Education Program at IAIN Parepare. Using a quasi-experimental method with a one-group pretest–posttest design, the study involved a single group of students as participants. Data were collected through a social intelligence test covering three main dimensions: social information processing, social awareness, and social skills. The data was analyzed using a paired sample t-test. The findings revealed a significant increase in students’ social intelligence after the implementation of the Tudang Sipulung learning model (p < 0.05), with the most notable improvements observed in collaborative and empathetic abilities that reflect Bugis cultural values such as siri’, pacce, and sipakatau. Practically, the results indicate that the Tudang Sipulung learning model serves as an effective pedagogical strategy to foster social intelligence and strengthen collaborative interactions grounded in local wisdom. Theoretically, this study reinforces Vygotsky’s social constructivist theory, emphasizing the role of social interaction in knowledge construction, while expanding the theoretical framework of local wisdom-based learning as a contextual approach in higher education.